Strengthening Public and Private Sector Collaboration for the Dumagat in Sta. Ines, Tanay, Rizal: Basis for A Four - Year IP Development Plan - Ana Christina M. dela Cruz (Iapa Proceedings Conference, 2019)
Providing a framework for exploring governance systems that range from policy or program-based inter-governmental cooperation (Makati and Tanay) to place-based collaboration with non-governmental stakeholders to public-private partnerships (PPP). Public-Private Partnership is geared towards financing, designing, implementing and operating facilities and services that are traditionally provided by the public sector. It embodies optimal risk allocation between the parties – minimizing cost while realizing project developmental objectives. Thus, the project is to be structured in such a way that the private sector gets a reasonable rate of return on its investment. This offers monetary and non-monetary advantages for the public sector. It addresses the limited funding resources for local IP development projects of the public sector, thereby allowing the allocation of public funds for other local priorities. The collaboration is geared for both sectors to gain improved efficiency and project implementation processes in delivering services to the IP community. Most importantly, it emphasizes Value for Money – focusing on reduced costs, better risk allocation, faster implementation, improved services and possible generation of additional revenue. A Four - year Indigenous People (IP) Development Plan for the Dumagat community is a concrete response to the United Nations’ 17 Sustainable Development Goals. Grounded in a vision that aims to transform our world - UN aspires to build a world free of poverty, hunger and disease, in which every woman and every girl enjoys full gender equality, where the environment is protected and where all people have access to quality education and decent work. The program is designed to create a sustainable community extension services for the IP community of Barangay Sta. Ines in Tanay, Rizal. The Dumagat community, characterized by lack of basic services, but open and willing to be organized to attain genuine and holistic development is the priority of the program. In the implementation, it will follow the different stages in community organizing to ensure the appropriateness of activities and training for community partners. Organizing the poorest of the poor can lead to empowerment. Also, it will allow them to become pro-active in ensuring the development